خليـلي وشـوقي في قصيدتيهما «مجسمه باميان» و «أبي الهول»؛ دراسة مقارنة - Raufi, Shah Rukh; Monib, Abdul Rab (Journal of Arabic Language and Literature (ALLAIS), 2023)
This research aims to review two poems by two of the stalwarts of Arabic and Persian poetry in the modern era, and the extent of influence and effect through comparative literature. It follows the applied analytical approach in light of the cultural and historical relations between the two literatures. Accordingly, he studies each poem, points out the similarities and differences between the two poems, and reveals some of the artistic aesthetics and creativity that characterize each poem. It became clear through the presentation of the two poems that the two poets expressed the past days and the ease and luxury that surrounded them, and the roughness and poverty that accompanied them. Then Shawqi sees the secret of the farmer in movement, moving forward, and leaning on oneself. The people of the country only serve their own people. As for Al-Khalili, he continued his complaints about the people of his time. Humanity has perverted and the mind is shackled in the era of scientific progress. It has become clear that Khalili, despite his knowledge of the Arabic language, and Shawqi being ahead of him in time, may have read Shawqi’s poem or been inspired by its subject, but he did not notice that he took one of the meanings. In addition to this, his treatment is radically different from him. When Shawqi pushes his statue to move, My boyfriend instructs him to hide from sight because the controlling madman might harm him and humanity has gone awry and does not redress injustices or shelter him; The poem is the tragedy of a people abandoned by humanity due to a brutal occupation.